Developing a Poverty Alleviation Acceleration Model Based on Sustainable Development Goals (SDGs) through Economic Improvement and Regional Financial Management (Journal of Economic Education, 2023)
The first year of the COVID-19 Pandemic greatly weakened the employment and unemployment situation in Semarang City. Based on previous researches, poverty can be overcome by increasing employment opportunities, social assistance, community empowerment, increasing education-based human resources and developing access to microfinance. Some previous investigations ignored the concept of Sustainable Development Goals (SDGs) as one of the concepts that can be carried out. SDGs are concepts that have prospects for overcoming poverty in Indonesia because those not only pay attention to economic aspects but also social and environmental aspects. The urgency of this research was the high poverty rate which indicated a low level of social welfare and required appropriate efforts and strategies to overcome. Poverty alleviation efforts must pay attention to all aspects, including economic, social and environmental in accordance with the Sustainable Development Goals (SDGs). Thus, the specific objectives of this research were 1) to analyze the development of poverty and the economy in the city of Semarang, 2) to analyze the role of economic growth and regional financial management against poverty, 3) to develop a poverty alleviation strategy model based on Sustainable Development Goals (SDGs). In realizing those objectives, this research employed a quantitative approach with the Partial Least Square (PLS) analysis method. Findings showed that the degree of fiscal decentralization did not directly have a significant direct effect on both economic growth and poverty. Furthermore, the balancing fund variable had a significant direct effect on both economic growth and poverty. Meanwhile, economic growth did not directly have a significant effect on poverty. Indirectly, neither the degree of fiscal decentralization nor the balance fund had a significant effect on poverty through economic growth